EDU WISATA UNTUK ANAK-ANAK SEKOLAH DASAR DAN PENGEMBANGAN PEMASARAN WISATA PETIK JERUK SELOREJO DENGAN MENGGUNAKAN MEDIA SOSIAL DI KECAMATAN DAU KABUPATEN MALANG - Andharu, Devito; Fadillah, Muhammad Reza Ishadi; Putra, Angga; Wijayanti, Regita (Politeknik Negeri Sriwijaya, 2023)
The partner of this community service activity is Orange Picking Tourism which is located at Selorejo Village, Dau District, Malang Regency, East Java. Tourist owners want to innovate related to their business by changing the concept of Orange Picking tourism to Eduwisata. Apart from that, there are efforts to change analog promotional methods to digital. So the partner problems, in this case Orange Picking Tourism, are: 1) Changing the concept of orange picking tourism to Eduwisata; 2) Analog promotional methods seem outdated and less effective. The short-term goal of community service activities is to increase tourist visits to the Orange Picking tourist attraction. Apart from that, it also develops links and matches between Dr. Soetomo University and the Jeruk Dau Picking Tourism. The implementation method used in community activity programs includes 1) training, there are two stages of training, namely, training on Edutourism material; 2) training in digital promotion methods using social media. The results of this community service activity are: 1) The formation of an Edutourism task force; 2) Promotion development using social media.